1992
DOI: 10.1002/ijc.2910500211
|View full text |Cite
|
Sign up to set email alerts
|

Food consumption and cancer of the colon and rectum in north‐eastern Italy

Abstract: The relation between dietary factors and the risk of colorectal cancer was investigated in a case-control study conducted in Pordenone province, North-eastern Italy, on 123 cases of colon cancer, 125 of rectal cancer and 699 controls admitted to hospital for acute, non-neoplastic or digestive disorders. Consistent positive associations were observed with more frequent consumption of bread (odds ratio, OR = 2.1 for colon and 2.2 for rectum for highest vs. lowest tertile), polenta (OR = 2.1 for colon, 1.9 for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
55
2
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 149 publications
(64 citation statements)
references
References 37 publications
(33 reference statements)
6
55
2
1
Order By: Relevance
“…In common with results from previous studies (Kearney et al, 1996;Boutron et al, 1996;Jain, 1998), no indication for a protective effect of cheese consumption against colorectal cancers was found; in contrast, higher cheese consumption was associated with a nonsignificantly elevated colon cancer risk. Similar increased colorectal cancer risk with cheese consumption was also reported in some previous studies (Bidoli et al, 1992;Fernandes et al, 1997).…”
Section: Discussionsupporting
confidence: 89%
“…In common with results from previous studies (Kearney et al, 1996;Boutron et al, 1996;Jain, 1998), no indication for a protective effect of cheese consumption against colorectal cancers was found; in contrast, higher cheese consumption was associated with a nonsignificantly elevated colon cancer risk. Similar increased colorectal cancer risk with cheese consumption was also reported in some previous studies (Bidoli et al, 1992;Fernandes et al, 1997).…”
Section: Discussionsupporting
confidence: 89%
“…The association between education and colon cancer risk is not clear for women. A correlation study (Baquet et al, 1991), a cross-sectional study (Faivre et al, 1989) and a case-control study (Bidoli et al, 1992) reported no association between education and colon cancer risk for women, while an inverse association was found in a crosssectional study (Williams and Horm, 1977), and in two cohort studies in Scandinavia (Pukkala and Teppo, 1986;Vagero and Persson, 1986) significant positive associations were reported. We did not find an association between education and colon cancer, which is consistent with the finding that health differences between SES categories for women are Kunst et al, 1993), probably because of relatively small differences in education within the female population.…”
Section: Discussionmentioning
confidence: 95%
“…Correlation (Baquet et al, 1991) and crosssectional (Williams and Horm, 1977;Faivre et al, 1989) studies did not show consistent associations, but case-control (Papadimitriou et al, 1984;Ferraroni et al, 1989;Bidoli et al, 1992) and cohort studies (Pukkala and Teppo, 1986;Vagero and Persson, 1986;Leon, 1988) showed predominantly positive associations between SES and colon cancer risk. In these studies hardly any adjustment was made for potential confounders.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Table 1 contains 30 case -control studies that had at least 99 cases and reported on meat intake (Benito et al, 1990;Bidoli et al, 1992;Centonze et al, 1994;Dales et al, 1979;Gerhardsson et al, 1991;Graham et al, 1978;Haenszel et al, 1973Haenszel et al, , 1980Hu et al, 1991;Iscovich et al, 1992;Kampman et al, 1995Kampman et al, , 1999Kato et al, 1990;Kune et al, 1987; La Vecchia (1992) 248 Italy Yes I R þ beef & pork; C-ve Centonze et al (1994) 118 Italy Yes H NS Dales et al (1979) 99 US Blacks -I N S Gerhardsson et al (1991) 559 Sweden Yes H C and R þ meats Graham et al (1978)) 586 USA (NY) -I N S Haenszel et al (1973) 179 Japanese in Hawaii -L CRC þ meat Heanszel et al (1980) 588 Japan --NS Hu et al (1991) 336 China Yes -NS Iscovich et al (1992) 110 Argentina Yes H NS Kampman et al (1995) 312 Netherlands Yes H NS Kampman et al (1999) 1542 USA Multicentre --NS Kato et al (1990) 221 Japan -I N S Kune et al (1987) 715 Australia Yes -C þ beef men, not women R þ lamb women, not men La Vecchia et al (1988) 575 N. Italy Yes -RR 2.0 CRC for meat but 3.0 for pasta þ rice La Vecchia et al (1996) 1326 N. Itlay -H CRC þ (1.6) for red meat Lee et al (1989) 203 Singapore Yes H NS Lyon et al (1988) 246 Utah, USA Yes -NS Macquart-Moulin et al (1986) 399 France Yes I NS Manousos et al (1983) 100 Greece Yes -CRC þ beef and lamb Miller et al (1983) 542 Canada Yes -R þ beef (?) Muscat et al (1994) 511 USA --NS Peters et al (1989) 146 Los Angeles, USA Yes -NS Peters et al (1992) 746 Los Angeles, USA Yes H NS Steinmetz et al (1993)…”
Section: The Case -Control Studiesmentioning
confidence: 99%